A mixed-methods study of maternal health care utilisation in six referral hospitals in four sub-Saharan African countries before and during the COVID-19 pandemic. Issue 2 (16th February 2022) - Banke-Thomas, Aduragbemi; Semaan, Aline; Amongin, Dinah; Babah, Ochuwa; Dioubate, Nafissatou; Kikula, Amani; Nakubulwa, Sarah; Ogein, Olubunmi; Adroma, Moses; Anzo Adiga, William; Diallo, Abdourahmane; Diallo, Lamine; et al.
Abstract : Introduction: In sub-Saharan Africa, referral hospitals are important sources of key maternal health services, especially during a crisis such as the COVID-19 pandemic. This study prospectively assessed the effect of the COVID-19 pandemic on maternal health service utilisation in six large referral hospitals in Guinea, Nigeria, Tanzania and Uganda during the first year of the pandemic. Methods: Mixed-methods design combining three data sources: (1) quantitative data based on routine antenatal, childbirth and postnatal care data collected March 2019–February 2021, (2) qualitative data from recurring rounds of semi-structured interviews conducted July 2020–February 2021 with 22 maternity skilled heath personnel exploring their perceptions of service utilisation and (3) timeline data of COVID-19 epidemiology, global, national and hospital-level events. Qualitative and quantitative data were analysed separately, framed based on the timeline analysis and triangulated when reporting. Results: Three periods including a first wave, slow period and second wave were identified. Maternal health service utilisation was lower during the pandemic compared with the prepandemic year in all but one selected referral hospital. During the pandemic, service utilisation was particularly lower during the waves and higher or stable during the slow period. Fear of being infected in hospitals, lack of transportation, and even when available, high cost of transportation and service closures were key reasons affecting utilisation during the waves. However, community perception that the pandemic was over or insinuation by Government of the same appeared to stabilise use of referral hospitals for childbirth. Conclusion: Utilisation of maternal health services across the continuum of care varied through the different periods and across countries. In crisis situations such as COVID-19, restrictions and service closures need to be implemented with consideration given to alternative options for women to access and use services. Information on measures put in place for safe hospital use should be communicated to women.